(untitled) (Praxis Educativa, 2017)
In this article, we review the main limits of modern democracy under the influence of economic relationships within a capitalist society, and we focus on the Chilean democracy. We also consider the influence that this democracy has over schools and their task of forming students for citizenship. In contrast, we mention those social and school experiences that by proposing collective goals and forms of participation question the elitism and individualism present in current forms of democracy. In such context, we discuss the contributions of the Chilean student protests to students’ citizenship and democratic education and we conclude that they have opened them an opportunity to rethink democracy, have allowed them new spaces for youth political participation, and have enabled experiences for the democratization of their schools.